PENERAPAN MODEL PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS V SD NEGERI 009 DELIK - Maulani, Novia Dwi; Lazim N, Lazim N; Kurniaman, Otang (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : this research do it because study result of social science from students SDN 009 Delik grades V very bad. The KKM in the school about 72. There are 27 students in the class but just 6 students (22,22%) reach the point of KKM. while 21 student (77,78%) not reach get it. With class scores 55,70. The purpose from research is to increase result and process social science learning at students of SDN 009 Delik grades V in using learning model of role playing. The result of this research get average base score about 55,70 increase about 36,30% to be 75,92. At cycle 2 average student score have increase too about 54,92% to be 86,29. At the complete clasical base score of social science mayor about 22,22% (not passed). After used model of role playing in cycle 1 get increase result in complite clasical score about 66,67% (still not passed) and in cycle 2 get increase result of complite clasical score about 92,59% (passed). The teacher activity in 1st metting in cycle 1 in percentage about 61,11% with enough category, 2nd metting increase to be 83,33% with good category. The teacher activity 1st metting in cycle 2 have 88,89% with very good category, 2nd metting increase to be 91,67% with very good category.The student activity ties 1st metiing in cycle 1 have 58,33% with enough category, and 2nd metting increase to be 63,88% with enough category. The student activity 1st metting in cycle 2 have 77,78% with good category, 2nd metting increase to be 86,88% with very good category.Key Words: role playing, learning result of social science